Pitfalls of supervised feature selection - Pawel Smialowski; Dmitrij Frishman; Stefan Krämer (2009)
Pitfalls of supervised feature selection Pawel Smialowski1,2,∗, Dmitrij Frishman1,2 and Stefan Kramer3 1Department of Genome Oriented Bioinformatics, Technische Universitat Munchen Wissenschaftszentrum Weihenstephan, Am Forum 1, 85350 Freising, 2Helmholtz Zentrum Munich, National Research Center for Environment and Health, Institute for Bioinformatics, Ingolstadter Landstrase 1, 85764 Neuherberg and 3Institut fur Informatik/I12, Technische Universitat Munchen, Boltzmannstr. 3, 85748 Garching b. Munchen, Germany